Komunikasi Pemasaran Coffee Shop Costa di Luwuk Kabupaten Banggai: Marketing Communications of Costa Coffee Shop in Luwuk, Banggai Regency - Adrian Kede, Adrian Kede (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2025)
This study aims to find out the marketing communication of Costa Coffee Shop in Luwuk, Banggai Regency. The method used is a qualitative method with data collection using observation, interview and documentation techniques. The results of this study show that Marketing communication carried out by Coffeshof Costa is through the AIDA (Attention, Interest, Desire, and Action) theoretical approach. In conclusion, Coffeshof Costa Marketing Communication in Luwuk City through the following strategies: personal branding using social media Instagram (Ig) the next @nolkilo account name that attracts consumers is the architecture of buildings with classic, modern nuances, the image of the coffee taste, sea views, affordable coffee prices, other facilities in the form of billiard tables and representative parking lots.Keywords: Communication, Marketing